Interim analysis of the Registry for Load and Management of Medication Overuse Headache (RELEASE): A multicenter, comprehensive medication overuse headache registry. (May 2022) - Park, Hong-Kyun; Chu, Min Kyung; Oh, Sun-Young; Moon, Heui-Soo; Song, Tae-Jin; Lee, Mi Ji; Kang, Jin-Ju; Hong, Yooha; Cho, Soo-Jin
Background: Characteristics, disabilities, and optimal management of medication overuse headache remain uncertain. This study aimed to elucidate the clinical characteristics of patients with medication overuse headache enrolled in a medication overuse headache registry in Korea. Methods: The Registry for Load and Management of MEdicAtion OveruSE Headache (RELEASE), a cross-sectional prospective observational study including seven referral headache centers in Korea, started enrolling adult patients with medication overuse headache in April 2020. Data included information on headache characteristics, burden on daily function, depression, anxiety, history of acute and preventive medications, and treatment strategies. Results: A total of 229 patients (85.6% females; mean age, 45.5 ± 13.5 years) were enrolled by June 2021. The average durations of chronic headaches and medication overuse were 6.5 and 4.3 years, respectively. In the past month before enrollment, patients had headaches for 25 days and severe headaches for 12 days, and used acute medications for 20 days. Patients were disabled in 66.8 days in the past 3 months and had moderate/severe depression and anxiety in 56% and 35%, respectively. The proportion of patients on preventive treatments increased from 38% to 93% during the study period. Conclusions: RELEASE study reflects the current management status and opportunities to improve the quality of care in patients with medication overuse headache.